VD_FINDINFO Arrêt / 2024 / 409 vom 2. Mai 2024 - VD Tribunal cantonal (2024)
RENTE D'INVALIDITÉ, COMPARAISON DES REVENUS, REVENU SANS INVALIDITÉ, CALCUL, ADMISSION DE LA DEMANDE | 28 LAI, 29 LAI, 16 LPGA